2017
DOI: 10.21451/1984-3143-2017-ar983
|View full text |Cite
|
Sign up to set email alerts
|

Leporinus elongatus induced spawning using carp pituitary extract or mammalian GnRH analogue combined with dopamine receptor antagonists

Abstract: Several studies have been developed to support the replacement of the crude carp pituitary extract (CPE) by synthetic products for induced reproduction of South American rheophilic species. However, results have been quite heterogeneous and there is no consensus or a routine use of synthetic products in these species. Thus, the aim of this study was to evaluate the ovulatory process in L. elongatus using different protocols of hormonal induction. Thus, fifteen wild mature females maintained at the Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Regarding this concern, studies developed in our laboratory have shown that the failures occur as a result of the hormonal induction process causing final maturation with migration and breakdown of the germinal vesicle (GVBD), but it is insufficient to cause ovulation (Criscuolo‐Urbinati et al., 2012). This type of failure had previously been demonstrated in carps (Jalabert et al., 1977), in other tropical rheophilic species, such as matrinxã ( Brycon amazonicus ) (Hainfellner et al., 2012), piau ( Leporinus friderici ) (De Souza et al., 2020), piapara ( Leporinus elongatus ) (Pereira et al., 2018) and piaçu ( Leporinus macrocephalus ) (Pereira et al., 2017), and all these descriptions shows the presence of unovulated GVBD oocytes retained in the ovaries.…”
Section: Introductionsupporting
confidence: 52%
“…Regarding this concern, studies developed in our laboratory have shown that the failures occur as a result of the hormonal induction process causing final maturation with migration and breakdown of the germinal vesicle (GVBD), but it is insufficient to cause ovulation (Criscuolo‐Urbinati et al., 2012). This type of failure had previously been demonstrated in carps (Jalabert et al., 1977), in other tropical rheophilic species, such as matrinxã ( Brycon amazonicus ) (Hainfellner et al., 2012), piau ( Leporinus friderici ) (De Souza et al., 2020), piapara ( Leporinus elongatus ) (Pereira et al., 2018) and piaçu ( Leporinus macrocephalus ) (Pereira et al., 2017), and all these descriptions shows the presence of unovulated GVBD oocytes retained in the ovaries.…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, the intermediate reproductive performance obtained using 1,000 μg sGnRHa/kg highlights that future approaches testing dopamine inhibitors together with sGnRHa may change the current scenario. Even unusual and much higher than that the doses used for hormonal induction for neotropical (Acuña & Rangel, 2009; Pereira et al., 2016, 2018; Souza et al., 2018, 2020; Viveiros et al., 2013), cyprinids (Podhorec et al., 2016; Podhorec, Socha, Sokolowska‐Mikolajczyk, Policar, Svinger, Drozd, et al., 2012; Podhorec, Socha, Sokolowska‐Mikolajczyk, Policar, Svinger, Gosiewski, et al., 2012) and salmonids fishes (Arabaci et al., 2004), the 1,000 μg sGnRHa/kg treatment resulted in fertility and hatching rates above 90%, indicating that the use of this synthetic treatment is not a problem for this species in this concern.…”
Section: Discussionmentioning
confidence: 94%
“…Concerning possible reasons for ovulation failures, we observed that only the unspawned females of the fractioned CPE group (and all individuals) retained GVBD oocytes (meiosis resumption) in the ovaries, while all unspawned females from other groups retained only oocytes with intact germinal vesicles. This specific type of failure, which causes GVBD but not ovulation, was in deep studied using fractioned CPE doses in common carp (Jalabert et al., 1977) and in some tropical reophilic species, such as matrinxã ( Brycon amazonicus ) (Hainfellner et al., 2012), piau ( Leporinus friderici ) (Souza et al., 2020), piapara ( Leporinus elongatus ) (Pereira et al., 2018) and piaçu, ( Leporinus macrocephalus ) (Pereira et al., 2016). All of these descriptions mentioned unovulated GVBD oocytes retained in the ovaries, but it is still unknown the reasons for such partial failure.…”
Section: Discussionmentioning
confidence: 99%
“…For the congener species H. edentatus (Carvalho, ), GSI values reported for mature females were also relatively low (6.4%), indicating that the maparás may present small GSI values in comparison to other tropical migratory fish. The GSI values of mature females of Brycon orbignyanus (Ganeco et al, ), Piaractus mesopotamicus (Romagosa, Paiva, Godinho, & Storfer, ), Pseudoplatystoma fasciatum (Romagosa et al, ), Prochilodus lineatus (Hainfellner, Souza, et al, ), Leporinus piau (Araújo, Oliveira, Costa, & Novaes, ), Salminus hilarii (Honji et al, ; Moreira et al, ), Rhamdia quelen (Reidel et al, ), Brycon amazonicus (Hainfellner, de Souza, Munoz, & Batlouni, ) and Leporinus elongatus (Pereira, Boscolo, Moreira, & Batlouni, ) were 15%, 15%, 15%, 19%, 20%, 16%, 10%, 15% and 16% respectively. The relatively small GSI values of species belonging to the Hypophthalmus genus may be associated with the small celomic cavity and the displacement of the organs towards the ventral part of the animal, whereas the caudal portion of the animal is entirely occupied by muscles, which is associated with its high fillet yield (Souza & Inhamuns, ), and also attributable to the fact that these species do not form fat deposits; rather, the fat is diffused in muscle tissue, giving the fillet its high fat content (Carvalho, ).…”
Section: Discussionmentioning
confidence: 99%